PROFESSIONAL COMPETENCE IS A KEY CONDITION FOR IMPROVING THE QUALITY OF EDUCATION OF FUTURE SPECIALISTS IN THE AGRICULTURAL AND TECHNICAL FIELD - Torchuk, Mikhailo; Mushenyk, Iryna; Zbaravska, Lesya (European Science, 2024)
The article analyzes the theoretical principles that form the basis of the concept of teaching physics to students of agricultural and technical educational institutions. The main methods for implementing the professional orientation of teaching physics t